HerMES: SPIRE detection of high-redshift massive compact galaxies in GOODS-N field - Cava, A.; Rodighiero, G.; Pérez-Fournon, I.; Buitrago, F.; Trujillo, I.; Altieri, B.; Amblard, A.; Auld, R.; Bock, J.; Brisbin, D.; Burgarella, D.; Castro-Rodríguez, N.; et al. (Wiley-Blackwell Publishing Ltd., 2010)
Wehave analysed the rest-frame far-infrared properties ofa sample of massive (M* > 1011 M?) galaxies at 2 ? z ? 3 in the Great Observatories Origins Deep Survey-North (GOODS-N) field using the Spectral and Photometric Imaging Receiver (SPIRE) instrument aboard the Herschel Space Observatory. To conduct this analysis we take advantage of the data from the Herschel Multi-tiered Extragalactic Survey (HerMES) key programme. The sample comprises 45 massive galaxies with structural parameters characterized with HST NICMOS-3. We study detections at submm Herschel bands, together with Spitzer 24-µm data, as a function of the morphological type, mass and size. We find that 26/45 sources are detected at MIPS 24 µm and 15/45 (all MIPS 24-µm detections) are detected at SPIRE 250 µ with disc-like galaxies more easily detected. We derive star formation rates (SFRs) and specific star formation rates (sSFRs) by fitting the spectral energy distribution of our sources, taking into account non-detections for SPIRE and systematic effects for MIPS derived quantities. We find that the mean SFR for the spheroidal galaxies (~50-100M? yr-1) is substantially (a factor ~3) lower than the mean value presented by disc-like galaxies (~250-300M? yr-1). © 2010 The Authors. Journal compilation © 2010 RAS.